DAMPAK PORTOFOLIO ASET TEKNOLOGI INFORMASI PEMANUFAKTURAN TERHADAP EFISIENSI OPERASIONAL DENGAN LINGKUNGAN INDUSTRI SEBAGAI VARIABEL PEMODERASI - Berlina Yudha Pratiwi; Wahyu Agus Winarno (Universitas Jember, 2013)
Manufacture Information Technology Asset Portfolios is a document contains some information technology investments to manufacture asset that can be used as a reference in determining the right business strategy for the purpose or performance to be achieved, in this case operational efficiency or organizational innovation.The industrial of environment where a firm competes will have a moderating effect on the relation between manufacture information technology asset portfolios with operational efficiency or organizational innovation. This research aims to identify and analyze the industrial environment influence of the relation between manufacture information technology asset portfolios with operational efficiency. This research is quantitative, and using secondary data in the form of annual report of manufacturing companies in Indonesia from 2009-2011. Determination of the sample in this study using purposive sampling criteria are manufacturing companies revealed that manufacture information technology asset in the annual report company. Data analysis was performed with the classical assumption test and hypothesis testing with moderating regression analysis (MRA) method. The results of the research showed that the industrial of environment statistically has positive and significant influence to the relation between manufacture information technology asset portfolios with operational efficiency. Keywords:manufacture information technology asset portfolios, operational efficiency, and industrial environment.